2020
DOI: 10.1080/10717544.2020.1841337
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiolabeled nanostructured lipid carrier systems containing imatinib mesylate on NIH-3T3 and CRL-1739 cells

Abstract: The aim of current study is to develop new nanostructured lipid carrier systems (NLCSs) containing imatinib mesylate (IMT) and evaluate their targeting efficiency on NIH-3T3 as fibroblast cells and CRL-1739 as gastric adenocarcinoma cells with radiolabeled formulations. Three formulations (F1-IMT, F2-IMT and F3-IMT) were prepared and radiolabeled with 1 mCi/0.1 mL of [ 99m Tc]Tc. The effect of reducing and antioxidant agents on radiolabeling process was evaluated and radiochemical purity of formulations was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The radiolabeling results are in agreement with those of previous studies performed on radiolabeled SLNs ( Figure 4 ). 40 Although higher radiolabeling stability values were obtained in saline than in the cell culture medium ( Figure 5 ), this difference showed no statistical significance ( p ≥ 0.05). In this study, all of the radiolabeled SLN formulations were stable in saline and cell culture media with radiolabeling efficiencies of over 80%, and these results showed that radiolabeled SLN formulations are proper for CB studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The radiolabeling results are in agreement with those of previous studies performed on radiolabeled SLNs ( Figure 4 ). 40 Although higher radiolabeling stability values were obtained in saline than in the cell culture medium ( Figure 5 ), this difference showed no statistical significance ( p ≥ 0.05). In this study, all of the radiolabeled SLN formulations were stable in saline and cell culture media with radiolabeling efficiencies of over 80%, and these results showed that radiolabeled SLN formulations are proper for CB studies.…”
Section: Discussionmentioning
confidence: 87%
“… 44 In our studies, lipid-based formulations containing cancer drugs showed no cytotoxic effects on human epithelial carcinoma cell lines; these findings are in agreement with our results. 40 , 45 Therefore, TRZ-loaded SLN formulations can be considered safe and valuable drug delivery systems for healthy cells in the diagnosis and treatment of breast cancer for future in vivo studies due to their high biocompatibility and nontoxic profiles. When used in the diagnosis of breast cancer, the prepared TRZ-SLN formulations will be radiolabeled with 99m Tc, and their toxic effect on cells will be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al used a mixture of acetone:ethanol (1:1) as the aqueous phase in their studies [20,21]. Based on this information, water, ethanol, and acetone mixtures in various proportions as the aqueous phase were used in our previous work, and as a result of the characterization studies of the formulations, it concluded that the water:acetone:ethanol mixture works effectively as the aqueous phase [22]. So, herein, water and water:acetone:ethanol mixture were used as the aqueous phase.…”
Section: Discussionmentioning
confidence: 99%